Fixed point theory in RWC–Banach algebras - Banaś, Józef; Krichen, Bilel; Mefteh, Bilel; O’Regan, Donal (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we prove some fixed point results for the sum and the product of nonlinear continuous operators acting on an RWC–Banach algebra. Our result is formulated in terms of topological conditions on the operators. An illustrative example on an RWC–Banach algebra, which is not a WC–Banach algebra, is provided.